Sociodemographic determinants of good sexual and reproductive health (SRH) knowledge among secondary school children in Kuantan, Pahang, Malaysia - Raja Ismail, Raja Nurul Najwa; Minhat, Halimatus Sakdiah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Adolescence being a transition phase from a child to an adult, commonly associated with high-risk sexual behaviours, which put them at risks of sexually transmitted diseases (STD), HIV and unwanted pregnancy. All these risks can be prevented by having adequate knowledge on sexual and reproductive health (SRH). Hence, this study aimed to determine the sociodemographic determinants of good SRH knowledge among secondary school children in Kuala Kuantan, Pahang Malaysia. Methods: A cross-sectional study was conducted among 687 secondary school children in Kuala Kuantan, Kuantan, Pahang, using self-administered questionnaire. A multistage cluster sampling was employed to recruit the respondents. Three levels of analysis were conducted to describe the characteristics of the respondents and determining the determinants of good SRH knowledge. Data was analysed using Statistical Package of IBM SPSS Statistics Version 24 and the p value was set to be less than 0.05. Results: The proportion with good SRH knowledge was 58.4%. Upper secondary school age group (AOR 7.142, 95% CI: 4.830, 10.560) and smokers (AOR 2.597, 95% CI: 1.348, 5.004) were found to be significant determinants of good SRH knowledge. Conclusions: The percentage of respondents with good SRH knowledge was just slightly above average. As expected, older school children has the strongest likelihood of having good SRH knowledge. Whether the good SRH knowledge is contributed by the existing SRH curriculum is unclear and requires further exploration. In view of the alarming SRH issues involving younger school children, strategic plan are needed to instil the knowledge at earlier age.